2015
DOI: 10.1101/gr.182444.114
|View full text |Cite
|
Sign up to set email alerts
|

Systematic interaction network filtering identifies CRMP1 as a novel suppressor of huntingtin misfolding and neurotoxicity

Abstract: Assemblies of huntingtin (HTT) fragments with expanded polyglutamine (polyQ) tracts are a pathological hallmark of Huntington's disease (HD). The molecular mechanisms by which these structures are formed and cause neuronal dysfunction and toxicity are poorly understood. Here, we utilized available gene expression data sets of selected brain regions of HD patients and controls for systematic interaction network filtering in order to predict disease-relevant, brain region-specific HTT interaction partners. Start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…In plasma from HD patients, brain‐derived 24‐OH cholesterol deficiency has been found, 40 and impaired cholesterol synthesis in the CNS has also been observed in a HD mouse model 41 . Further, evidence suggests that polyglutamine toxicity may be countered by high mobility group box proteins HMGB1/2 42 —homologs of the HMGA1, 43 a pathway that was also disrupted in our study.…”
Section: Discussionsupporting
confidence: 67%
“…In plasma from HD patients, brain‐derived 24‐OH cholesterol deficiency has been found, 40 and impaired cholesterol synthesis in the CNS has also been observed in a HD mouse model 41 . Further, evidence suggests that polyglutamine toxicity may be countered by high mobility group box proteins HMGB1/2 42 —homologs of the HMGA1, 43 a pathway that was also disrupted in our study.…”
Section: Discussionsupporting
confidence: 67%
“…All five members of the collapsin response mediator protein (Crmp) family, also known as dihydropyrimidinase-related proteins (Dpysl), were also enriched ( Figure 5 B). A study identified Crmp1 as a suppressor of huntingtin toxicity ( Stroedicke et al., 2015 ). Apart from confirming these known aggregate constituents, our data provide a large number of new proteins with potential links to HD ( Table S3 A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we extracted genes, whose corresponding proteins were reported to be physically associated with HTT, from the HDNetDB database. We recently demonstrated that HTT interactors tend to be enriched in proteins that influence the toxicity of mHTT, and provide favourable candidates for the identification of molecular modifiers of HD 74 .…”
Section: Resultsmentioning
confidence: 99%